Introducing a Scalable WhatsApp Banking Solution in South Africa - Sukdeo, Revaaj (University of the Witwatersrand, Johannesburg, 2025)
A significant portion of the South African population is not only unbanked but also underbanked. The introduction of a USSD based WhatsApp Banking solution that is easy to use and affordable can provide another channel in the Digital Banking space to help alleviate this issue. This writing focused on ascertaining the optimal design and commercialisation route for such a solution, using the qualitative approach to extract information from industry expert. The findings indicate that user perception of platform security coupled with customer education is key for market acceptance while the inclusion of transactional services and streamlined menu flows will enhance usability.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; USSD Banking; WhatsApp Banking; Financial Inclusion; Digital Banking; SDG-9: Industry, innovation and infrastructure